Unraveling FOXO3a and USP18 Functions in Idiopathic Pulmonary Fibrosis through Single-Cell RNA Sequencing of Mouse and Human Lungs - Wang, Ban; Pan, Jichun; Liu, Zhonghui (Global Medical Genetics, 2023)
Background Idiopathic pulmonary fibrosis (IPF) is identified as a chronic, progressive lung disease, predominantly marked by enhanced fibroblast proliferation and excessive deposition of extracellular matrix. The intricate interactions between diverse molecular pathways in fibroblasts play a crucial role in driving the pathogenesis of IPF.Methods This research is focused on elucidating the roles of FOXO3a, a transcription factor, and USP18, a ubiquitin-specific protease, in modulating fibroblast functionality in the context of IPF. FOXO3a is well-known for its regulatory effects on cellular responses, including apoptosis and oxidative stress, while USP18 is generally associated with protein deubiquitination.Results Our findings highlight that FOXO3a acts as a critical regulator in controlling fibroblast activation and differentiation, illustrating its vital role in the pathology of IPF. Conversely, USP18 seems to promote fibroblast proliferation and imparts resistance to apoptosis, thereby contributing to the exacerbation of fibrotic processes. The synergistic dysregulation of both FOXO3a and USP18 in fibroblasts was found to significantly contribute to the fibrotic alterations characteristic of IPF.Conclusion Deciphering the complex molecular interactions between FOXO3a and USP18 in fibroblasts provides a deeper understanding of IPF pathogenesis and unveils novel therapeutic avenues, offering a promising potential for not just halting but potentially reversing the progression of this debilitating disease.
Keywords: idiopathic pulmonary fibrosis; FOXO3a; USP18; apoptosis; oxidative stress